Morfodinâmica de uma praia estuarina: o caso de Beja (Abaetetuba-Pará) - SOUSA, Maria Bárbara Pereira de (2019)
The Beja beach (Abaetetuba - Pará), has a vulnerability to erosion, intensified mainly by anthropic processes such as the disorderly occupation of the shore. For this purpose, we aimed to analyze the morphodynamics of Beja beach. The methodology consisted of: (1) the acquisition of beach topography data, hydrodynamic data, sampling of surface sediments and with portable traps, and beachside observation for classification of the beach, through two campaigns (rainy season, 25-27/07/2016 and in dry season, 15/11/2016); (2) laboratory analysis for the granulometric separation; (3) data processing for morphodynamics classification and morphometric parameters using Grapher and Excel softwares and grading of granulometry using the SysGran software. The Beja beach was classified as intermediate, being Transverse Banks (Ω = 3,06) during the rainy season and Low Tide Terrace (Ω = 2,12) in the dry period, but presenting strong dissipative characteristics. The central sector stood out, showing an erosive characteristic (-21,13 m3/m of sedimentary volume in november) that can be explained by the sector location, the phenomenon of supermoon and the layout of the border. Sediment transport was higher in the rainy season and during the flood tide (23,60 g/h/m2) due to the intensification of local hydrodynamics and rainfall. In relation to the classification and typology of the border, the Beja beach was divided into sheltered Orla not urbanized or Class A and sheltered Orla in process of urbanization or Class B, the latter being the most comprehensive classification of the beach. Due to the increasing process of urbanization, such as the construction of the shoreline, a change in the hydrodynamics and configuration of Beja beach was caused.